Cell death in tumor microenvironment: an insight for exploiting novel therapeutic approaches - Wenxin Wang; Tong Li; Kui Wu (Cell Death Discovery)
Abstract Cell death is critical in tumor biology. The common cancer therapies can cause cell death and alleviate tumor, while the cancer cells can develop a resistance to cell death and survive from the therapies. Thus, not only observing the alternative mechanisms of tumor cells resistant to cell death, but also understanding the intricate dynamics of cell death processes within the tumor microenvironment (TME), are essential for tailoring effective therapeutic strategies. High-throughput sequencing technologies have revolutionized cancer research by enabling comprehensive molecular profiling. Recent advances in single cell sequencing have unraveled the heterogeneity of TME components, shedding light on their complex interactions. In this review, we explored the interplay between cell death signaling and the TME, summarised the potential drugs inducing cell death in pre-clinical stage, reviewed some studies applying next-generation sequencing technologies in cancer death research, and discussed the future utilization of updated sequencing platforms in screening novel treatment methods targeted cell death. In conclusion, leveraging multi-omics technologies to dissect cell death signaling in the context of the TME holds great promise for advancing cancer research and therapy development.